Analysis of perception of emotion in a stressful situation using psychological and physiological measurements - Jayalakshmy Aarthi Ananthanarayanan (2013)
The purpose of this study was to identify any difference in terms of how participants perceive their feelings when performing a simple physical activity and eventually how well they perform in stressful and non-stressful conditions. Previous research states that participants in stressful situations tend to be anxious and thus perform their task poorly. However, a stressful situation need not induce anxiety as participants could perceive the situation positively and performance need not always deteriorate. In this study, 40 SSM undergraduate students were randomly allocated into 2 groups. They performed a darts throwing task over 3 trials- a baseline trial and 2 manipulation trials. In the experimental condition, stressors were introduced while in the control condition, the trials were conducted without the stressors. Results from the two- way repeated ANOVA showed significant differences between the stressed and non-stressed conditions in terms of the Heart rate ( p = .020) and perceived feeling scores (p = .042). However no significant difference was observed in the performance outcome (p = .651) at a significance level of p < .05. Contrast tests were done for heart rate and feeling scores which further confirmed the interaction effect (Trials x Groups). In this study, it was observed that participants under stressful situations perceived their emotions more negatively. However performance was not affected by this interpretation. It was concluded that there was indeed a difference in the perception of feelings as well as changes in heart rate between the groups but no significant difference in performance outcome.